Implementation of Internet of Things for Smart Traffic Management (International Journal of Food and Nutritional Sciences, 2022)
Intelligent cars can interact directly with junctions thanks to the use of roadside equipment connected via smart traffic management. Using IOT technology, sensors placed at strategic locations may gather information on high-traffic intersections and regions where automobiles are diverted. One of the biggest issues the world is now dealing with is urban transportation, particularly in large cities. The increase in traffic upon that road network cannot be adequately managed by previous traffic control technologies. In this paper author focuses on proposes a revolutionary Internet of Things-based intelligent traffic administration system that can replace existing traffic management systems and has the potential to significantly enhance traffic. The system is low cost, highly scalable, compatible, and easy to upgrade. It concluded that, Multiple IOT hardware characteristics have been used in the development of the Smart Traffic Management System. Utilizing the IOT platform, traffic optimization is accomplished by efficiently allocating varied amounts of time to each traffic light based on the number of cars on the route. In the future, a mobile application that is linked to a centralized server also notifies the closest rescue agency of the fire explosion as well as the location to take further steps. The origin user can also ask about the status of the incoming traffic on a specific node in the future.